Evaluation of Modular Power Converter Integrated with 5G Network - Sebastian Baba (MDPI AG, 2021)
This paper focuses on two key technical concepts, which may have a tremendous impact on future generations of power electronic converters: the Power Electronic Building Block (PEBB) concept, and the 5G/6G wireless data transfer. It is expected that these two trends may induce development of new cognitive of power electronic converters: Power Electronics 4.0. To investigate this concept, a Proof of Concept (PoC) of PEBB-based power converter integrated with a 5G network, was designed and tested. Study confirmed that power converter assembled from PEBB modules can compete with state-of-the-art devices. Moreover, test results indicates that several challenges related to PEBB and integration of power electronic equipment with 5G network has to be resolved, to enable growth of augmented power electronic converters, especially if wireless data transfer is meant for communication between PEBB modules.